A case of ricin poisoning following ingestion of Korean castor bean. Issue 4 (23rd March 2009) - Lim, H; Kim, H J; Cho, Y S
Abstract : Ricin is a member of a group of protein toxins whose cytosolic target is the 28S rRNA of the 60S ribosomal subunit. It was recently introduced as a weapon of terrorism in some countries. There is little evidence about the mechanism, diagnosis and treatment of ricin poisoning. The case history is reported of a patient with ricin poisoning who presented with nausea and vomiting following ingestion of Korean castor bean.